Designing an Intelligent Technical System That Provides Alerts When Dispensing Conflicting Medications - Hammida Misbah Salih; Saraa Daw Abudawia (AlQalam Journal of Medical and Applied Sciences, 2025)
The paper outlines the design of a technical system for dispensing conflicting medications to keep pace with technological advancements. This system aims to facilitate medication management and alert against dispensing drugs that interact with other medications, chronic diseases, or certain types of food, thereby helping to improve service efficiency and ensure patient safety, preventing them from unnecessary health risks by reducing human errors. Where medications are dispensed with an integrated mechanism to monitor conflicting drugs or those that interact with diseases, necessitating the development of a more comprehensive mechanism to ensure the safe dispensing of medications from the systems present in pharmacies within Libya. Keeping up with technological advancements and attempting to reduce the harm caused by dispensing medications that interact with each other, with the disease, or with the diet by pharmacies. The Modified Waterfall Model was used to develop and create this system, which is one of the well-known models. It was chosen for its flexibility in dealing with the system, allowing us to move to the next phase in the life cycle and revert to any previous phase according to changes in requirements. The system was analyzed and described in detail using the Unified Modeling Language (UML), clarifying the system’s flow, structure, and classifications. Subsequently, the system was designed, and its outputs were presented as required, in terms of databases and interfaces. It can be said that the system has achieved the goals for which it was designed by executing the required main functions, which are issuing smart alerts when dispensing medications that interact with other medications, chronic diseases, or certain types of food in a smooth and well-programmed manner. This system aims to enhance patient safety by issuing automated alerts during the medication dispensing process, particularly when any potential interaction between the dispensed medication and other medications (drug interactions), chronic medical conditions, or specific types of food that affect the absorption or efficacy of the medication is detected. The system relies on a continuously updated medical database maintained by a specialized data entry professional (doctor or pharmacist). The system issues immediate alerts, contributing to the reduction of medication errors, improving the quality of healthcare, and promoting a culture of safety in healthcare institutions.